Perancangan Sistem Layanan Grosir Warung Berbasis Website Dengan Metode Prototipe (Studi Kasus: Manjoo) - Oktavirani, Yurike; Jaman, Jajam Haerul; Rozikin, Chaerur (Jurnal Ilmiah Wahana Pendidikan, 2024)
The manjoo warung website is an online wholesale service website that can be ordered remotely. This website is expected to provide convenience in finding wholesale shop products at competitive prices. The manjoo warung website is a grocery stall service intended for shop owners who are going to open a grocery shop business. The survey data conducted in this study, it shows that many grocery shop owners are still having trouble finding distributors for their stalls. So manjoo proposed and designed an idea to be able to overcome the problem. In this study, website design only reached the interactive prototype stage. In designing this interactive prototype using the prototype method and testing using the technology acceptance model (TAM) method. The variables used for testing using the technology acceptance model (TAM) are perceived usefulness, perceived ease of use, actual system use, behavioral intention to use, and self-efficacy. From the results of the normality test, and others, it is found that the influential variables are self-efficacy which directly influences perceived ease of use, perceived ease of use which directly influences perceived usefulness, perceived ease of use with behavioral intention of use, and behavior intention of use with actual system of use. Keywords: Prototype, User Interface, Technology Acceptance Model, Grocery Store, Website